2014
DOI: 10.3855/jidc.3412
|View full text |Cite
|
Sign up to set email alerts
|

Differential Early Secreted Antigen Target (ESAT) 6 kDa–induced IFN-γ and SOCS1 expression distinguishes latent and active tuberculosis

Abstract: Introduction: Expression of Suppressor of cytokine signaling (SOCS)-1 molecules is increased in patients with tuberculosis (TB). Early Secreted Antigen Target (ESAT)-6 kDa -induced IFN-γ responses indicate Mycobacterium tuberculosis infection. The effect of ESAT6-stimulation on SOCS1 in the host is not known. Methodology: Healthy asymptomatic controls had a negative (n = 16) or a positive ( n = 13) tuberculin skin test (TST). ESAT6-induced IFN-γ responses classified these controls as positive (EC ESAT6 IFN-γ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…It was reported that miR-29 was increased in serum, sputum and CD4 + T cells from active TB patients (14,15,44), which suggested that miR-29 plays important roles in TB infection. It has been demonstrated that IFN-γ is associated with latent TB infection and is a direct target of miR-29b (23,24,45,46). Our data showed that an increased miR-29b level was concomitant with a decreased IFN-γ expression in CWD-Mtb group compared with wild Mtb group.…”
Section: Discussionsupporting
confidence: 52%
“…It was reported that miR-29 was increased in serum, sputum and CD4 + T cells from active TB patients (14,15,44), which suggested that miR-29 plays important roles in TB infection. It has been demonstrated that IFN-γ is associated with latent TB infection and is a direct target of miR-29b (23,24,45,46). Our data showed that an increased miR-29b level was concomitant with a decreased IFN-γ expression in CWD-Mtb group compared with wild Mtb group.…”
Section: Discussionsupporting
confidence: 52%
“…SOCS proteins are negative regulators of the JAK/STAT pathway (Alexander & Hilton, 2004), and accumulating evidence indicates that they are involved in the control of the cytokine networks responsible for adequate and efficient innate immune responses (Yoshimura et␣al , 2007). For example, SOCS1 expression is significantly increased in patients with tuberculosis, where SOCS1 transcript levels are correlated with disease severity (Masood et␣al , 2012; Masood et␣al , 2013; Masood et␣al , 2014). SOCS1, 4, and 5 are highly expressed in mice infected with hypervirulent Mtb (Manca et␣al , 2005).…”
Section: Introductionmentioning
confidence: 99%